Cognitive Mobility: Labor Market Responses to Supply Shocks in the Space of Ideas - Borjas, George J.; Doran, Kirk B. (Journal of Labor Economics, 2015)
Knowledge producers conducting research on a particular set of questions may respond to supply and demand shocks by shifting resources to a different set of questions. Cognitive mobility measures the transition from one location to another in idea space. We examine the cognitive mobility flows unleashed by the influx of Soviet mathematicians into the United States after the collapse of the Soviet Union. The data reveal that American mathematicians moved away from fields that received large numbers of Soviet émigrés. Diminishing returns in specific research areas, rather than beneficial human capital spillovers, dominated the cognitive mobility decisions of knowledge producers.